Increasing Business Income Of Dairy Goat Crossbreed Etawah Farming In Payageli Village Deli Serdang District - Sitepu, Sukma Aditya; Marisa, Julia (Talenta Publisher Universitas Sumatera Utara, 2019)
The purpose of this community service were to give an introduction to the farmers about income analysis of Etawah Crossbred Goat business and to know the farmers’, with various ownership level, income in Payageli Village Deli Serdang. The implementation of community service was expected to improve the capability and knowledge of the goat milk farmers, to analyze and separate between the acceptance component and cost components in the same maintenance period. The information could then facilitate the farmers on how to calculate the total income in a period of raising the goat, resulting in the imprvement of farmers’ welfare. The results showed that the farmers have an ability to analysis their business income, so that they learned how to minimised their production cost to increase their income.